2016
DOI: 10.1007/s12026-016-8813-y
|View full text |Cite
|
Sign up to set email alerts
|

Is explantation of silicone breast implants useful in patients with complaints?

Abstract: In this review, we present a critical review of the existing literature reflecting the results of explantation of silicone breast implants in patients with silicone-related complaints and/or autoimmune diseases. A literature search was performed to discuss the following issues: which clinical manifestations and autoimmune diseases improve after explantation, and what is the course of these complaints after explantation. Next, we reviewed studies in which the effect of explantation on laboratory findings observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 47 publications
3
67
1
10
Order By: Relevance
“…Heavy metals adversely affect enzymes, DNA, and leukocyte respiration; can be toxic to muscle, brain, lungs, kidneys, liver, blood, and nerves; and when present in excess amounts can mimic multiple sclerosis, Parkinson's, Alzheimer's, and muscular dystrophy (21) . Clinical correlates reported in implant recipients include (but are not limited to) hair loss, recurrent infections in a variety of sites, weakness, fatigue, muscle twitching, nail cracking and splitting, cognitive dysfunction, a multitude of other nervous system disorders (e.g., paresthesias; dysesthesias; dizziness; gait imbalance); and abdominal pain, nausea, constipation, and loose stools from dysfunction of the myenteric plexus) (1,2,3,4,5,6,7,12,16,20,22) . i.…”
Section: Illness In Implant Recipientsmentioning
confidence: 99%
See 3 more Smart Citations
“…Heavy metals adversely affect enzymes, DNA, and leukocyte respiration; can be toxic to muscle, brain, lungs, kidneys, liver, blood, and nerves; and when present in excess amounts can mimic multiple sclerosis, Parkinson's, Alzheimer's, and muscular dystrophy (21) . Clinical correlates reported in implant recipients include (but are not limited to) hair loss, recurrent infections in a variety of sites, weakness, fatigue, muscle twitching, nail cracking and splitting, cognitive dysfunction, a multitude of other nervous system disorders (e.g., paresthesias; dysesthesias; dizziness; gait imbalance); and abdominal pain, nausea, constipation, and loose stools from dysfunction of the myenteric plexus) (1,2,3,4,5,6,7,12,16,20,22) . i.…”
Section: Illness In Implant Recipientsmentioning
confidence: 99%
“…In actuality, the presence or absence of autoantibodies in patients with these devices has no relevance for diagnosing siliconeinduced disease (4,16,20,22) . In yet another publication Tervaert and colleagues try to prop up their mistakes by publishing a review of commingled conditions (both explicit and/or loosely defined), all of which lack any unifying clinical features but are all supposed to represent silicone-induced toxicity based on a haphazard response to explanation (7) . Their "kitchen sink" approach is devoid of even the most basic elements of proper investigative methodology including, but not limited to: chronological disease development over time (which has been documented to be a dose-response curve); rupture versus non- rupture analysis; duration of implantation analysis; a more comprehensive, reproducible and consistent data base for recording the ailments of their patients; prior exchange surgeries; intrinsic validity analysis; explanation results that take into account the duration of prior implantation; and the well-known fact that a patient fulfilling criteria for a classical connective tissue disease doesn't necessarily imply that one has arrived at the correct diagnosis (16.20) .…”
Section: Why Asia Is Fantasia (An Improvisation)mentioning
confidence: 99%
See 2 more Smart Citations
“…De Boer and colleagues [31] suggested that at least in those with breast implants, explantation of the silicone prosthesis improved the complaints in 75 % of the patients. Such improvement was only infrequently observed without additional therapy with immunosuppressive therapy in those developing a full-blown autoimmune disease [32].…”
mentioning
confidence: 99%